Detection of a Cryptic 25 bp Deletion and a 269 Kb Microduplication by Nanopore Sequencing in a Seemingly Balanced Translocation Involving the LMLN and LOC105378102 Genes - Wang, Yanan; Zhao, Zhenhua; Fu, Xinyu; Li, Shufang; Zhang, Qiuyan; Kong, Xiangdong (Frontiers in Genetics, 2022)
Preimplantation genetic testing (PGT) played a critical role for balanced translocation carrier to obtain the normal embryo. Especially for the carrier with phenotypic abnormity, identifying the precise breakpoints allowed us to reveal the disrupted genes. In this study, a seemingly balanced translocation 46, XX, t(3;6)(q29;q26) was firstly detected using conventional karyotype analysis. In order to locate the precise breakpoints, whole genome DNA was sequenced based on nanopore GridION platform, and bioinformatic analyses were further confirmed by polymerase-chain-reaction (PCR) and copy number variation (CNV). Nanopore sequencing results were consistent with the karyotype analysis. Meanwhile, two breakpoints were successfully validated using PCR and Sanger sequencing. LOC105378102 and LMLN genes were disrupted at the breakpoint junctions. Of note, we found the apparently balanced translocation was in fact unbalanced due to a cryptic 269 kilobases (Kb) duplication and a 25 bp microdeletion at the breakpoints of chromosome (chr) 6 and chr 3, respectively. Furthermore, 269 Kb duplication was also confirmed by CNV analyses. In summary, nanopore sequencing was a rapid and direct method for identifying the precise breakpoints of balanced translocation in spite of low coverage (3.8×). In addition, cryptic deletion and duplication were able to be detected at single-nucleotide level.